The promise and perils of mainstreaming intersectionality in the Colombian peace process - González Villamizar, Juliana (International journal of transitional justice, 2021)
This article examines the extent to which mainstreaming intersectionality in the Colombian Truth Commission (CEV) serves the feminist aim of producing social transformations by exposing patriarchal, racialized and class-based structures of oppression. Analysing the mainstreaming of intersectionality as a site of struggle exposes the interlocking dynamics of inequality and ontological impositions that block Indigenous and Afro-descendant women’s full participation at the CEV. Ongoing dialogues with five Indigenous and/or Afro-descendant Colombian activists centrally inform this analysis. All the activists utilize the gender, woman, family and generation approach, which is anchored in the shared cosmological reference points of Indigenous and Afro-descendant women. The peril of mainstreaming intersectionality appears when it is used in a shallow manner that severs a structural intersectional analysis from a political intersectional analysis. The promise of intersectionality can only be realized through a holistic understanding and application of both its structural and political dimensions.